The 10-week of aerobic-functional training improves fasting blood sugar, insulin resistance, and lipid profile in patients with diabetic peripheral neuropathy: A randomized controlled trial - Beigi Sharif; Shabkhiz Fatemeh; Kordi Mohammadreza; Haghi-Ashtiani Bahram; Hashemi-Madani Nahid (Sciendo, 2022)
Study aim: This study aimed to investigate the effect of a 10-week of combined training course on concentrations of blood sugar, Insulin Resistance (HOMA-IR), and lipid profile in patients with diabetic peripheral neuropathy.